Influence of wet activation of used inorganic binder on cyclically refreshed water glass moulding sands hardened by microwaves - Stachowicz, Mateusz; Granat, Kazimierz (China foundry, 2016)
The paper presents the research results of using an innovative method to reclaim the waste moulding sands containing water glass. Two of the examined processes are connected with “dry” or “wet” activation of inorganic binder in waste moulding sand mixtures physically hardened by microwave radiation. The sand mixtures consisting of high-silica sand and water-glass with average molar module 2.5, were subjected to the following cyclical process： mixing the components, compacting, microwave heating, cooling-down, thermally loading the mould to 800 °C, cooling-down to ambient temperature, and knocking-out. After being knocked-out, the waste moulding sands were subjected to either dry or wet activation of the binder. To activate thermally treated inorganic binder, each of the examined processes employed the surface phenomenon usually associated to mechanical reclamation. The study also covered possible use of some elements of wet reclamation to rehydrate waste binder. To evaluate the effectiveness of the two proposed methods of waste binder activation, selected strength and technological parameters were measured. After each subsequent processing cycle, the permeability, tensile strength and bending strength were determined. In addition, the surface of activated sand grains was examined with a scanning electron microscope. Analysis of the results indicates that it is possible to re-activate the used binder such as sodium silicate, and to stabilize the strength parameters in both activation processes. Permeability of the refreshed moulding sands strongly depends on the surface condition of high-silica grains. The wet activation process by wetting and buffering knocked-out moulding sands in closed humid environment makes it possible to reduce the content of refreshing additive in water-glass. The moulding sands cyclically prepared in both processes do not require the addition of fresh high-silica sand. The relatively high quality achieved in the refreshed moulding sands allows them to be reused for manufacture of next moulds. Thus, the two proposed methods for cyclically processing used moulding sands containing sodium silicate, subject to microwave hardening, are suitable for economic and ecological circulation moulding mixtures.